Board of Editor - Journal of Infrastructure & Facility Asset Management (Journal of Infrastructure & Facility Asset Management, 2020)
Board of Editor PATRON :  Dean - Faculty of Civil, Environmental, Earth Sciences - ITS.Head Training Center Management & Functional Position - Ministry of PWPH. RESPONSIBLE  :   Head of Department  – Civil Engineering Department - ITSBOARD OF EDITOR               Chief Editor                          :               Ria Asih Aryani Soemitro ITS, Indonesia                                                                         h-index (GS = 10)Founding Editor                    :               Hitapriya Suprayitno ITS, Indonesia                                                                               h-index (GS =   8)         Managing Editor                   :               Trihanyndio Rendy Satrya ITS, Indonesia                                                                        h-index (GS =  2)                                                           Mahendra Andiek Maulana ITS, Indonesia                                                                       h-index (GS =  2)Editor                                  :               Data Iranata  ITS, Indonesia                                                                                          h-index (GS =   3)                                                            Alex Abdi Chalik PUPR, Indonesia                                                                                   h-index (GS =    -)                                                            Danang Parikesit UGM, Indonesia                                                                                   h-index (GS =   7)                                                           Maimunah Sapri UTM, Malaysia                                                                                      h-index (GS = 15)                                                           Wahyu Caesarendra UBS, Brunei Dar es Salam                                                               h-index (GS = 17) Address                             :                Editor JIFAM – Room  J - 201                                                          Departement of Civil Engineering                                                                     Institut Teknologi Sepuluh Nopember                                                          ITS Campus, Sukolilo, Surabaya 60111                                                          Email: jurnal.jifam@gmail.com                                                            Website: https://iptek.its.ac.id/index.php/jifam